Arctic Intermediate Water in the Nordic Seas, 1991–2009. (October 2017) - Jeansson, Emil; Olsen, Are; Jutterström, Sara
Abstract: The evolution of the different types of Arctic Intermediate Water (AIW) in the Nordic Seas is evaluated and compared utilising hydro-chemical data from 1991 to 2009. It has been suggested that these waters are important components of the Norwegian Sea Arctic Intermediate Water (NSAIW), and of the dense overflows to the North Atlantic. Thus, it is important to understand how their properties and distribution vary with time. The AIWs from the Greenland and Iceland Seas, show different degrees of variability during the studied period; however, only the Greenland Sea Arctic Intermediate Water (GSAIW) shows an increasing temperature and salinity throughout the 2000s, which considerably changed the properties of this water mass. Optimum multiparameter (OMP) analysis was conducted to assess the sources of the NSAIW. The analysis shows that the Iceland Sea Arctic Intermediate Water (ISAIW) and the GSAIW both contribute to NSAIW, at different densities corresponding to their respective density range. This illustrates that they flow largely isopycnally from their source regions to the Norwegian Sea. The main source of the NSAIW, however, is the upper Polar Deep Water, which explains the lower concentrations of oxygen and chlorofluorocarbons, and higher salinity and nutrient concentrations of the NSAIW layer compared with the ISAIW and GSAIW. This shows how vital it is to include chemical tracers in any water mass analysis to correctly assess the sources of the water mass being studied. Highlights: The properties of the Greenland Sea Arctic Intermediate Water in 2009 indicate an Atlantic-dominated water type. The Norwegian Sea Arctic Intermediate Water is considerably older than the AIW found in the Greenland and the Iceland Seas. Optimum multiparameter analysis applied to the NSAIW. The main source to the NSAIW is the upper Polar Deep Water. ISAIW and GSAIW contribute to different density layers of NSAIW, via isopycnal advection.